Spinal cord injury without radiologic abnormality in children. Issue 4 (April 2015) - Boese, Christoph Kolja; Oppermann, Johannes; Siewe, Jan; Eysel, Peer; Scheyerer, Max Joseph; Lechler, Philipp
<x xml:space="preserve">Abstract</x> BACKGROUND Spinal cord injury in children is associated with severe morbidity and immense socioeconomic burden. In spinal cord injury without radiologic abnormalities (SCIWORA), magnetic resonance imaging (MRI) can detect intramedullary or extramedullary pathologies or show absence of neuroimaging abnormalities. However, the prognostic and therapeutic consequences of specific MRI patterns are unclear. A comprehensive systematic literature search was performed to examine patient characteristics and imaging patterns of pediatric SCIWORA and to evaluate the prognostic value of a MRI-based classification system. METHODS MEDLINE, Cochrane Central Register of Controlled Trials, and Google Scholar were searched for studies on SCIWORA in children. Inclusion criteria were (1) traumatic spinal cord injury with acute neurologic deficit, (2) absence of fractures and/or dislocations of the spine, and (3) an immature skeleton or age of less than 18 years. MRI patterns and clinical course were correlated. RESULTS Forty articles reporting 114 patients were identified. At admission, neurologic deficit assessed by the American Spinal Injury Association impairment scale was A in 28%, B in 17%, C in 31%, and D in 25%. At final follow-up, these were 19%, 6%, 10%, and 16%, respectively. In 43%, no MRI abnormalities (Type I) were detected, and 57% exhibited abnormal scan results (Type II): 6% revealed extraneural (Type IIa), 38% intraneural (Type IIb), and 13% combined abnormalities (Type IIc). At admission and follow-up, American Spinal Injury Association impairment scale differed significantly between the imaging types. CONCLUSION This systematic review emphasizes the prognostic value of spinal MRI for children with SCIWORA. It highlights the role of the MRI classification system in improving the comparability and interpretability. LEVEL OF EVIDENCE Systematic review, level IV.